Beyond Disease: Happiness, Goals, and Meanings among Persons with Multiple Sclerosis and Their Caregivers - Delle Fave, Antonella; Bassi, Marta; Allegri, Beatrice; Cilia, Sabina; Falautano, Monica; Goretti, Benedetta; Grobberio, Monica; Minacapelli, Eleonora; Pattini, Marianna; Pietrolongo, Erika; Valsecchi, Manuela; Amato, Maria Pia; et al. (Frontiers in Psychology, 2017)
The experience of persons with multiple sclerosis (MS) and their caregivers is usually investigated in terms of emotional distress and health-related quality of life , while well-being indicators remain largely underexplored. In addition, findings are often interpreted from the clinical perspective, neglecting socio-cultural aspects that may crucially contribute to individuals’ functioning. At the methodological level, most studies rely on scaled instruments, not allowing participants to freely express their needs and resources. Based on the bio-psycho-social perspective endorsed by the International Classification of Functioning well-being indicators were investigated among 62 persons with MS (PwMS), their 62 caregivers and two control groups, matched by age and gender. Participants completed the Positive Affect Negative Affect Schedule (PANAS), Satisfaction with Life Scale (SWLS), and the Eudaimonic and Hedonic Happiness Investigation instrument (EHHI). EHHI provides information on participants’ happiness, goals and meanings through scaled and open-ended questions, contextualized within major life domains. No relevant differences emerged among PwMS and caregivers, compared with the respective control groups, as concerns life domains associated with happiness, goals and meaning. Participants across groups prominently mentioned family, highlighting its intrinsic value and its relevance as a sharing context; health did not represent a major theme for PwMS; community, society and religion/spirituality issues were substantially neglected by all participants. PwMS and caregivers reported lower levels of positive affect than their control groups, while no differences emerged for negative affect, happiness and meaningfulness levels in life and across domains, and satisfaction with life. Results suggest that the experience of MS is associated with well-being in relevant life domains, such as family and close relationships. Although PwMS and caregivers identified a lower number of goals and meaning-related opportunities compared to control groups, they showed a positive adjustment to disease through the development of personal and family resources. These assets are often undervalued by health professionals and social institutions, while they could be fruitfully exploited through the active involvement of PwMS and their families as expert and exemplary informants in initiatives aimed at promoting the well-being of individuals and communities.